If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 5 + 3x + 5 = 40 Reorder the terms: 5 + 5 + 12x + 3x = 40 Combine like terms: 5 + 5 = 10 10 + 12x + 3x = 40 Combine like terms: 12x + 3x = 15x 10 + 15x = 40 Solving 10 + 15x = 40 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 15x = 40 + -10 Combine like terms: 10 + -10 = 0 0 + 15x = 40 + -10 15x = 40 + -10 Combine like terms: 40 + -10 = 30 15x = 30 Divide each side by '15'. x = 2 Simplifying x = 2
| 1/2y(6) | | f(x)=4x^3-5x^4 | | 8-bx=-16 | | 2(x+3)=1+4x | | 8(-3x+1)=-10(x-4)-14x | | 0.5x-6=-24 | | 2x^2+16x+42=10 | | 3(3x+13)=9x-8 | | (x+31)-5=3x | | 46.17=x+0.15x+0.065x | | 1.8q=3.24 | | 2X-3X+7Z=9 | | 6(x-3)=3(3x-2) | | 2=(3x+4)(1-x) | | 20=14-6 | | 7log(x)=32 | | E(x)=lx-1l+lx+3l | | 1.8+7s=9.1 | | 9.25t+9=15.5t+14 | | (3x-6)+27=-15 | | Y=-2x^2-13x+7 | | -4/5-9=1 | | -4/5-6=4 | | 6m+10=2 | | 3x-11=2x-(5-x) | | 6x(3x-2)(x+7)=0 | | 7(2x-3)-4(x+5)=8(x-1)+5 | | 5+4(w+2)=(w+7)+1 | | 8s^2+14s=15 | | 5x=21-x | | 5x=21+x | | 4x-4=-12+10 |